Experience of Applying TNF--inhibitors (Adalimumab and Etanercept) while Treating a Patient with Juvenile Arthritis and Eye Failure - T. I. Korovkina (Union of pediatricians of Russia, 2015)
The article presents a seven-year-long monitoring of a patient with juvenile arthritis and eye problems who is refractory to the standard basic immunosuppressive drugs therapy. High efficiency of both tumor necrosis factor (TNF) receptor blocker etanercept and recombinant antibody to TNF- adalimumab for joint syndrome therapy was noted. It is emphasized that in case of rheumatoid uveitis it is more appropriate to use adalimumab as a drug with proven efficacy. When selecting the biological agent it is necessary to pay attention to changes in the organ of vision, including those that can be interpreted as the outcome of the previously experienced uveitis, and to the laboratory data such as antinuclear antibodies and antibodies to native and denatured DNA, which may serve as predictors of eye damage.